Students’ Perspective in Applying Cognitive and Metacognitive Strategies Through Listening Comprehension - Yulyani, Rani Dewi (Jurnal Ilmiah Humanika, 2018)
Listening skill is a receptive skill. As a receptive skill, students only have to receive and comprehend the materials, no need to have a production on it. However, Listening become a crucial material for students to comprehend the language, especially for EFL (English as a Foreign Language) learners. Although, it is a receptive skill, it is important to use the strategy to encourage students to be more active in learning a language. Thus, students will easily to comprehend the language that they learn. Due to the issue, the study was aimed to determine students‘ perspective on the implementation of cognitive and metacognitive strategies through listening comprehension. This study involved 35 participants on the second semester from English department, faculty of letter Pamulang University. The instruments of the data finding were the paper-based Linkert scale survey and the reflective questions related to students‘ perception on the implementation of the cognitive and metacognitive strategies through their listening comprehension: first, what are the difficulties on listening comprehension?, second, how the cognitive and metacognitive strategies help to encounter the difficulties? The data finding showed that the students gave positive responses to the cognitive and metacognitive strategies of the improvement on their listening comprehension. Yet, the cognitive and metacognitive strategies implication is needed for further research.